TREN PUBLIKASI TENTANG PARIWISATA BERKELANJUTAN - Hendi Prasetyo (Pringgitan, 2022)
Sustainable tourism is a tourism concept that can have a positive impact and reduce negative impacts on the environment, social, culture, and economy of local communities in the long term. This study aims to determine the trend of publications related to sustainable tourism. This research was conducted using quantitative methods and the analysis was carried out using bibliometrics. In this study, data on sustainable tourism published in 2020-2021 was obtained by utilizing the Google Scholar database in the Publish or Perish application, then processed using VOSviewer. The results of the study show that there are 176 publications related to sustainable tourism published in 2020-2021. Based on the results of the analysis that has been carried out, it was found that of the 281 authors involved in writing related to sustainable tourism in 2020-2021, there were only 4 authors who met the co-authorship network threshold, namely (indriyanto, mn) and (kawatak sy) included in the Cluster. 1, (ginting, n) in Cluster 2, and (rosalia, f) in Cluster 3. Meanwhile, in the co-occurrence network of a total of 931 terms, there are only 3 terms that meet the threshold and are incorporated in 1 Cluster. namely Indonesia, Pariwisata, dan Pariwisata berkelanjutan. Based on the research above, the researcher recommends the next author to raise topics related to sustainable tourism in Indonesia in particular or Indonesian tourism in general.Keywords:     Trends, Publications, Sustainable Tourism